Melanin and melanoma: Updating molecular structure and photothermal therapy - Stockert, J.C. (2021)
Melanin pigment and melanoma are two fields of increasing interest and relevance in biomedical research. Melanins are ubiquitous biopigments with strong adaptive value and multiple functions. In mammals, melanin corresponds to eumelanin (brown-black) and pheomelanin (yellow-red), and is found mainly in the skin and derivatives, retinal pigmented epithelium, and central nervous systems (neuromelanin, in substantia nigra, locus coeruleus, etc.). Melanin also occurs in the malignant melanoma, which is one of the most aggressive and therapy-resistant tumors in veterinary and human medicine. Several chemical structures have been proposed for eumelanin, but there is still no agreement about its molecular organization. Two models, namely a flexible linear chain, and a rigid planar chain, are the structures that better agree with physico-chemical properties of eumelanin. The latter model, which appears as the most plausible structure, corresponds to a benzoquinone derivative of the porphycene ring, and explains the broad-band light absorption, antioxidant capacity, electric conductivity, and photothermal effect, as well as the multilayered and graphite-like organization shown by X-ray crystallography and electron microscopy. In addition to traditional oncologic treatments and recent immunological and gene therapy advances, photodynamic and photothermal approaches represent novel therapeutic modalities for melanoma. In the latter case, since eumelanin is practically the ideal photothermal sensitizer, the massive vibrational decay from photo-excited electronic states after NIR irradiation induces an immediate and highly efficient heating response that results in coagulative necrosis of the tumor. This allows repetitive treatments due to the remaining melanin contained in tumoral melanophages. Although the evolution and prognosis of the advanced melanoma is still a concern, new physical procedures can now be applied.